Los juegos tradicionales en la integración de los niños de 4 a 5 años del centro de educación inicial Pekelandia, ciudad de Riobamba - Santillán Alarcón, Sofía Antonela (2024)
This research work is titled “Traditional Games in the Integration of Children Aged 4 to 5 Years at the Pekelandia Early Education Center, city of Riobamba”, whose general objective is to determine the importance of traditional games in the integration of children aged 4 to 5 years from the Pekelandia Initial Education Center. To collect theoretical information that helps support the problem posed, it was obtained from books, magazines, websites, and virtual libraries, which allowed the proposed objectives to be achieved. The research had a qualitative approach; its design was correlational, which allowed the goals established in the research to be met. Through the study of methods and techniques for analysis, the observation of the problem posed was carried out in person with 26 children, which made it possible to know the context in which they operate, along with the support of the teachers, which allowed us to deduce that traditional games are an essential integration tool for children, which teachers must take into account when planning educational activities.